Clinical and Economic Evaluation of Repository Corticotropin Injection: A Narrative Literature Review of Treatment Efficacy and Healthcare Resource Utilization for Seven Key Indications - Philbin, Michael (Adv Ther, 2017)
INTRODUCTION: Repository corticotropin injection (RCI; H.P. Acthar(®) Gel; Mallinckrodt Pharmaceuticals Inc., Hampton, NJ) is a highly purified, prolonged-release porcine preparation of adrenocorticotropic hormone (ACTH) analogue that is FDA-approved for treatment of 19 autoimmune and inflammatory disorders. The diverse physiological actions of RCI at the melanocortin receptors (MCRs) affect processes involved in inflammation, pigmentation, steroidogenesis, and immunomodulation. Although RCI has been approved to treat inflammatory and autoimmune diseases for more than 60 years, recent progress in understanding both MCRs and the effects of RCI in modulating immune responses has led to increased interest in RCI as a therapeutic choice. The objective of this narrative literature review is to summarize key clinical and economic data on RCI treatment of seven disorders: infantile spasms (IS), multiple sclerosis (MS) relapses, proteinuria in nephrotic syndrome, rheumatoid arthritis (RA), dermatomyositis/polymyositis (DM/PM), systemic lupus erythematosus (SLE), and symptomatic sarcoidosis based on published literature and product information. An extended report is available as the Academy of Managed Care Pharmacy (AMCP) Formulary dossier for H.P. Acthar(®) Gel. METHODS: Key studies of clinical efficacy and healthcare utilization and cost from 1956 to 2016 are summarized. RESULTS: The evidence supports the efficacy of RCI across the seven indications. RCI is effective as a first-line therapy for IS. For the other six conditions, RCI may improve clinical outcomes during exacerbations or when the condition is resistant to conventional treatments. Use of RCI is associated with reduced use of biologics, corticosteroids, and disease-modifying antirheumatic drugs. Initiation of RCI therapy in patients with IS, MS, RA, SLE, or DM/PM has been associated with lower post-therapy healthcare utilization and medical costs, including decreases in hospitalizations, hospital length of stay, outpatient visits, and emergency department visits. CONCLUSION: The evidence suggests that RCI may improve inflammatory and autoimmune disease control and patient quality of life, particularly in complex patients, and yield healthcare cost savings that demonstrate the medicine’s value. FUNDING: Mallinckrodt Pharmaceuticals Inc. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12325-017-0569-9) contains supplementary material, which is available to authorized users.